Phylogenetic placement of Bahusandhika, Cancellidium and Pseudoepicoccum (asexual Ascomycota) - Pratibha, J.; Prabhugaonkar, A.; Hyde, K.d.; Bhat, D.j. (Phytotaxa, 2014)
Most hyphomycetous conidial fungi cannot be presently placed in a natural classification. They need recollecting and sequencing so that phylogenetic analysis can resolve their taxonomic affinities. The type species of the asexual genera, Bahusandhika, Cancellidium and Pseudoepicoccum were recollected, isolated in culture, and the ITS and LSU gene regions sequenced. The sequence data were analysed with reference data obtained through GenBank. The DNA sequence analyses shows that Bahusandhika indica has a close relationship with Berkleasmium in the order Pleosporales and Pseudoepicoccum cocos with Piedraia in Capnodiales; both are members of Dothideomycetes. Cancellidium applanatum forms a distinct lineage in the Sordariomycetes.